O ensino da ginástica em universidades públicas no Nordeste: notas sobre práticas de ensino, pesquisa e extensão - Kássia Mitally da Costa Carvalho; Carolina Godoy; Kizzy Fernandes Antualpa; Roberta Santos Kumakura; Marco Antonio Coelho Bortoleto; Laurita Marconi Schiavon (Caderno de Educação Física e Esporte, 2026)
BACKGROUND: This research is part of a nationwide study aimed at mapping the teaching, research, and extension practices related to Gymnastics in public higher education institutions (HEIs), conducted by the Gymnastics Research Group of the School of Physical Education at the State University of Campinas. The investigation is based on the premise that HEIs are responsible for educating professionals who will contribute to the development of gymnastics in different contexts. Therefore, their academic background and professional activities may reveal relevant aspects for understanding the development of this field. OBJECTIVE: To analyze the academic background and professional activities of faculty members working in the field of Gymnastics at public Higher Education Institutions (HEIs) in the Northeast region of Brazil, as well as the teaching, research, and extension activities they conduct. METHODS: A qualitative-quantitative documentary analysis with a descriptive-exploratory approach was carried out. The study examined the Pedagogical Political Projects and curricular structures of the HEIs, as well as the faculty members’ Lattes Curricula, using descriptive statistics and content analysis. RESULTS: Among the 42 faculty members from the 24 public HEIs studied, 12 (28.6%) had studied Gymnastics during their graduate education, and 14 (33.3%) had Gymnastics as the subject of their academic publications, supervision of academic works, and/or extension projects. CONCLUSION: The work of qualified and specialized faculty members in the field has an impact on professional practice, scientific production, and knowledge dissemination, which are necessary conditions for local and regional development. The predominance of “non-specialist” faculty members in the region does not favor the advancement of Gymnastics in the Northeast, a situation that differs from that observed in the South and Southeast regions of Brazil.